Functional and Structural Impairments in the Perirhinal Cortex of a Mouse Model of CDKL5 Deficiency Disorder Are Rescued by a TrkB Agonist - Ren, Elisa; Roncacé, Vincenzo; Trazzi, Stefania; Fuchs, Claudia; Medici, Giorgio; Gennaccaro, Laura; Loi, Manuela; Galvani, Giuseppe; Ye, Keqiang; Rimondini, Roberto; Aicardi, Giorgio; Ciani, Elisabetta (Frontiers in Cellular Neuroscience, 2019)
Cyclin-dependent kinase-like 5 (CDKL5) deficiency disorder (CDD) is a severe X-linked neurodevelopmental encephalopathy caused by mutations in the CDKL5 gene and characterized by early-onset epilepsy and intellectual and motor impairments. No cure is currently available for CDD patients, as limited knowledge of the pathology has hindered the development of therapeutics. Cdkl5 knockout (KO) mouse models, recently created to investigate the role of CDKL5 in the etiology of CDD, recapitulate various features of the disorder. Previous studies have shown alterations in synaptic plasticity and dendritic pattern in the cerebral cortex and in the hippocampus, but the knowledge of the molecular substrates underlying these alterations is still limited. Here, we have examined for the first time synaptic function and plasticity, dendritic morphology, and signal transduction pathways in the perirhinal cortex (PRC) of this mouse model. Being interconnected with a wide range of cortical and subcortical structures and involved in various cognitive processes, PRC provides a very interesting framework for examining how CDKL5 mutation leads to deficits at the synapse, circuit, and behavioral level. We found that long-term potentiation (LTP) was impaired, and that the TrkB/PLCγ1 pathway could be mechanistically involved in this alteration. PRC neurons in mutant mice showed a reduction in dendritic length, dendritic branches, PSD-95-positive puncta, GluA2-AMPA receptor levels, and spine density and maturation. These functional and structural deficits were associated with impairment in visual recognition memory. Interestingly, an in vivo treatment with a TrkB agonist (the 7,8-DHF prodrug R13) to trigger the TrkB/PLCγ1 pathway rescued defective LTP, dendritic pattern, PSD-95 and GluA2-AMPA receptor levels, and restored visual recognition memory in Cdkl5 KO mice. Present findings demonstrate a critical role of TrkB signaling in the synaptic development alterations due to CDKL5 mutation, and suggest the possibility of TrkB-targeted pharmacological interventions.